Comparison between two mixtures of lidocaine and bupivacaine for infraclavicular block: a double blind randomized trial - Jaber, El Kaissi; Amine, El Moqaddem; Mounir, Khalil; Hicham, Kechna; Moulay Ahmed, Hachimi; Jaouad, Laoutid (International Surgery Journal, 2020)
Background: We compare the two mixtures in terms of efficiency, analgesia, and side effects. Methods: 30 patients scheduled for upper limb surgery were randomized in 2 groups. the group A received a mixture of 50% lidocaine 2% and 50% of bupivacaine 0.5% the group B received a mixture of 75% lidocaine 1% and 25% of bupivacaine 0.5%. Volumes, block onset times, blocks duration times, analgesia, and toxicity were compared. Results: The volumes were equals in both groups. Sensory block onset was 5.43 min in the group A versus 6.73 min in the group B, motor block onset was 11.93 for the group A versus 13.46 min for the group B. Sensory block duration was 5.48 hours in the group A versus 4.05 hours for the group B (p=0.037), motor block duration was 7.75 hours for group A versus 5.50 hours for group B (p=0.014). Analgesia levels are equals between the two groups, there was no side effects listed. Conclusions: The use of low concentrated lidocaine and bupivacaine mixture induces an adequate anaesthesia and decreases the duration of motor block with a reduced level of pain and an equal level of analgesia.